The Impact of Inflation on the Medical and Hospital Money Transfers of the Neurosurgical Procedures of the Brazilian Unified Healthcare System from 2008 to 2017 - Magalhães, Marcelo José Silva de; Araújo, Graciella Lopes; Almeida, Letícia Pinheiro de; Soares, Wanessa Santos; Martins, Daniel Santos; Martins, Guilherme Duraes; Vasconcelos, Isadora Fonseca de; Delgado, Lara Cristina Lima; Oliva, Henrique Nunes Pereira; Magalhães, Aline Almeida de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Introduction There are more than 1,500 hospital procedures included in the Brazilian Unified Healthcare System's (SUS, in the Portuguese acronym) table, which is the reference for service payment provided by establishments serving the public health network, and they are stagnant. The underfinancing of procedures is so dramatic that in some cases the amounts paid by the SUS are even lower than the taxes generated by the costs of the same procedures in Brazilian private hospitals. This article aims to compare the evolution of the compensation of neurosurgical procedures by calculating the percentile of the lag in the values transferred to both neurosurgeons and hospitals, according to the SUS table, establishing the ideal and real values according to the current inflation, in a retrospective 9-year comparison.Methodology This is an observational, comparative, retrospective study, based on the values of medical and hospital money transfers of 25 neurosurgical procedures in 2008, which were corrected according to the 2017 National Consumer Price Index (IPCA, in the Portuguese acronym).Results Through this study, from 2008 to 2017, the transfers of medical fees regarding neurosurgical techniques are almost completely outdated. As examples, we can mention: the external/subgaleal ventricular shunt, with a deficit of 43.6%; the electrode implant for brain stimulation, with - 41.67%; and decompressive craniotomy, with - 32.21% in relation to the corrected value. Only 4 of the 25 neurosurgeries present a value above that predicted by the IPCA, one of them being cerebral aneurysm embolization larger than 1.5 cm with a narrow neck (+ 8.0%). Regarding the money transfers to hospitals, all procedures are 43.6% lower than expected, since there was no readjustment in the amounts paid to the institutions in the analyzed period. For example, in 2008, for the transposition of the cubital nerve, R$ 267.30 were transferred, and the same amount was maintained in 2017; and, for the surgical treatment of compressive syndrome in osteofibrous tunnel at carpal level (R$ 145.18), the amount also remained fixed throughout these 9 years.Conclusion Because they did not follow the evolution of the economy, in 80% of the surgeries, the neurosurgeons did not have their economic demands met regarding the procedures performed through SUS. And the data became even more alarming when the money transfers to hospitals were evaluated, since there was no evolution in the money transfers for any of the neurosurgeries evaluated.
Keywords: neurosurgery; inflation; medical fees; hospital costs